DISAIN DAN APLIKASI RANGKAIAN TRIGER SCR UNTUK PENYEARAH TERKENDALI SATU FASA - Effendi; Fitriady (J-Innovation, 2019)
This SCR trigger circuit was constructed by using Op-Amp LM324N, diodes, IC Regulator, and some others electronics equipment, this circuit used to activate SCR according to triggering angle desired by turning potentio on the duty cycle circuit, the changes of voltage value from potensio furthermore will be compared with the wave that produced by the sawtooth generator circuit with using an Op-Amp, it can producing an adjustable pulse waveform, futhermore connected to an isolation circuit in the form of a transformer which has a separate coil on the secondary side. This triggering circuit is designed to drive a single phase half wave controlled rectifier or full wave controlled rectifier that use a resistive load, as for the output waveform at the load is observed visually by using osciloscop, so that the level of accuracy produced will vary for testing at the same triggering angle by several different people.